2002
DOI: 10.1046/j.1365-2133.2002.04869.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cornified cell envelope in human hair follicle development

Abstract: These data indicate that, in terms of CCE formation, certain portions of the developing human hair follicle have already been determined in differentiation of the hair canal and cuticle at the hair peg stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
2
22
1
Order By: Relevance
“…Several lines of evidence suggest that DLK as well as its human homolog (also known as human leucine-zipper protein kinase (17)) or its rat homolog (MAPK upstream kinase (18)), a serine/threonine kinase originally isolated from mouse embryonic kidney (19), is another particularly interesting MAPKKK that could also be implicated in regulating keratinocyte differentiation. This hypothesis is supported by the finding that DLK mRNA and protein are specifically expressed in the differentiated granular layer of human epidermis and in the inner root sheath of hair follicles (20), which possess histological and histochemical characteristics comparable to those of keratinizing epidermal cells (21). In addition, the transient expression of wild-type DLK by the transfection of normal human keratinocytes cultured on plastic is associated with the detection of filaggrin in these cells (20), suggesting that DLK may play an active role in the mechanisms that regulate the terminal differentiation of epidermal keratinocytes.…”
supporting
confidence: 63%
“…Several lines of evidence suggest that DLK as well as its human homolog (also known as human leucine-zipper protein kinase (17)) or its rat homolog (MAPK upstream kinase (18)), a serine/threonine kinase originally isolated from mouse embryonic kidney (19), is another particularly interesting MAPKKK that could also be implicated in regulating keratinocyte differentiation. This hypothesis is supported by the finding that DLK mRNA and protein are specifically expressed in the differentiated granular layer of human epidermis and in the inner root sheath of hair follicles (20), which possess histological and histochemical characteristics comparable to those of keratinizing epidermal cells (21). In addition, the transient expression of wild-type DLK by the transfection of normal human keratinocytes cultured on plastic is associated with the detection of filaggrin in these cells (20), suggesting that DLK may play an active role in the mechanisms that regulate the terminal differentiation of epidermal keratinocytes.…”
supporting
confidence: 63%
“…Recent studies showed the typical pro-apoptotic effector caspases-3, -6, -7 are not activated during terminal differentiation in the epidermis, but skin-specific caspase-14, which is exclusively expressed in the stratum granulosum, is involved in the terminal differentiation [29,30]. Apoptosis of periderm cell, roof cell of hair canal, and terminal differentiated interfollicular epidermis share the same appearing order of precursor proteins [31][32][33]. Filaggrin, transglutaminase or ceramide generated in the terminal differentiated cells may trigger the apoptosis pathway [34][35][36][37].…”
Section: Discussionmentioning
confidence: 98%
“…TG1 remains restricted to the inner root sheath and the inner cells of the dermal outer root sheath; TG3 becomes restricted to the hair shaft, while TG5 expression overlaps with that of involucrin in the inner root sheath, the outer root sheath, and the hair shaft (284). CE formation is observed throughout the inner root sheath, in the inner cells of the dermal outer root sheath, and in the hair canal (17).…”
Section: A General Overview and Protein Expressionmentioning
confidence: 93%
“…The molecular events of CE development are believed to be almost identical in the epidermis and hair follicle (17). TG2 plays a role in stabilization of the dermoepidermal junction (7) but is not involved in cornification.…”
Section: A General Overview and Protein Expressionmentioning
confidence: 99%